Structural Characterization of Ferrihydrite/Hematite Nanocomposites and Their Arsenic Adsorption Properties - Nicolaza Pariona; Karla I. Camacho-Aguilar; Rodolfo Ramos-González; Arturo I. Martinez; Martin Herrera-Trejo (Adsorption Science & Technology)
A rich variety of ferrihydrite/hematite nanocomposites (NCs) with specific size, composition and properties were obtained in transformation reactions of 2-line ferrihydrite. Transmission electron microscopy observations showed that the NCs consist of clusters of strongly aggregated nanoparticles (NPs) similarly to a “plum pudding”, where hematite NPs “raisins” are surrounded by ferrihydrite “pudding”. The arsenic adsorption performance of the NCs can be modified for As(III) and As(V) removal, which depends on the NCs composition and the size of hematite NPs. It was found that adequate ferrihydrite/hematite NCs adsorb As(III) faster than ferrihydrite. Otherwise, for As(V), the adsorption exhibited by NCs is slower that for pure ferrihydrite. The data of adsorption isotherms fitted better to the Freundlich model for both As(III) and As(V) adsorption. For all the samples, the model revealed that chemical adsorption is the favorable adsorption process. Additionally, for the ferrihydrite/hematite NCs, the capacity of adsorption for As(III) is higher than for As(V). The high affinity of the NCs for the adsorption of As(III) makes them a good alternative for arsenic removal.